Smart scheduling on cloud for IoT-based sprinkler irrigation. Issue 1 (4th June 2020) - Mannan J., Mannar; S., Kanimozhi Suguna; M., Dhivya; T., Parameswaran
Abstract : Purpose: The purpose of this paper aims to reduce the manpower, electricity, and water consumption for irrigation. Design/methodology/approach: The IoT-based smart irrigation system designed with various sensors to collect farm field data, and stored all the data in the cloud for scheduling the irrigation. Findings: This system reduces the water and electricity consumption, and labor cost. Research limitations/implications: Difficult to implement on a small farm field with different crops. Practical implications: Crop type, soil type and environment data should be considered for better saving of water. Social implications: Reduces the water consumption, electricity, man power and increase production. Originality/value: The soil type, crop type and environment data have been added before irrigation. The climate data also included before scheduling. Dynamic changing of irrigation timings based on the climate and sensor data.